Corporate Taxation in the United States: The Post-War Experience - J.C.R. Rowley (Queen's University, Department of Economics, 1970)
The area of corporate taxation has stimulated a great deal of debate in both academic and political circles. On the political side, there have been those who argue that a corporation is only a legalistic creation and should not be regarded as a 'flesh-and-blood' person. This paper shall be concerned only with Federal taxes on corporations, although it is recognized that the system of dual sovereignity has raised questions of constitutionality in taxation areas between the Federal and state governments. A result of this has been the developing importance of the judicial branch of government in the taxation field, along with the legislative branch, as an interpretive body of no small significance.
Keywords: 330